High Tempers in High Places - Hickling, R.H. (Journal of Malaysian and Comparative Law, 1984)
There is no doubt about it, life in a small colonial society can present many problems. The present generation will not be familiar with the tetehy nature of colonial judges, yet even within living memory it is said that two British judges, sharing chambers in Ipoh, refused to speak to each other, and communicated by means of written memoranda, so deep was their mutual detestation. Vanity is one of the emblems of the judiciary.